Variability of the surface energy balance in permafrost-underlain boreal forest - Stuenzi, Simone Maria; Boike, Julia; Cable, William; Herzschuh, Ulrike; Kruse, Stefan; Pestryakova, Luidmila A.; Schneider von Deimling, Thomas; Westermann, Sebastian; Zakharov, Evgenii S.; Langer, Moritz (Biogeosciences, 2021)
Boreal forests in permafrost regions make up around one-third of the global forest cover and are an essential component of regional and global climate patterns. Further, climatic change can trigger extensive ecosystem shifts such as the partial disappearance of near-surface permafrost or changes to the vegetation structure and composition. Therefore, our aim is to understand how the interactions between the vegetation, permafrost and the atmosphere stabilize the forests and the underlying permafrost. Existing model setups are often static or are not able to capture important processes such as the vertical structure or the leaf physiological properties. There is a need for a physically based model with a robust radiative transfer scheme through the canopy. A one-dimensional land surface model (CryoGrid) is adapted for the application in vegetated areas by coupling a multilayer canopy model (CLM-ml v0; Community Land Model) and is used to reproduce the energy transfer and thermal regime at a study site (63.18946∘ N, 118.19596∘ E) in mixed boreal forest in eastern Siberia. An extensive comparison between measured and modeled energy balance variables reveals a satisfactory model performance justifying its application to investigate the thermal regime; surface energy balance; and the vertical exchange of radiation, heat and water in this complex ecosystem. We find that the forests exert a strong control on the thermal state of permafrost through changing the radiation balance and snow cover phenology. The forest cover alters the surface energy balance by inhibiting over 90 % of the solar radiation and suppressing turbulent heat fluxes. Additionally, our simulations reveal a surplus in longwave radiation trapped below the canopy, similar to a greenhouse, which leads to a magnitude in storage heat flux comparable to that simulated at the grassland site. Further, the end of season snow cover is 3 times greater at the forest site, and the onset of the snow-melting processes are delayed.